The Taylor polynomial of order #n# is the #(n+1)#-th partial sum of the Taylor series:

#f(x) = sum_(n=0)^oo (f^((n))(a))/(n!)(x-a)^n#

for #n=2# we have:

#d/dx sqrt(3+x^2) = x/sqrt(3+x^2)#

#d^2/dx^2 sqrt(3+x^2) = (sqrt(3+x^2) - x^2/sqrt(3+x^2))/(3+x^2) = 3/(3+x^2)^(3/2)#

So for #a=1#:

#f^((0))(1) = sqrt(3+1^2) = 2#

#f^((1))(1) = 1/sqrt(3+1^2) = 1/2#

#f^((2))(1) = 3/(3+1^2)^(3/2) = 3/8#

Then:

#T_2(x) = 2+1/2(x-1)+3/16(x-1)^2#

#T_2(x) = (32+8(x-1)+3(x-1)^2)/16#

#T_2(x) = (32+8x-8+3x^2-6x+3)/16#

#T_2(x) = (3x^2+2x+27)/16#